Evaluation of Bureaucratic Simplification Performance: Institutional, Human Resources, and Administrative Practices Analysis in Achieving Good Governance in Indonesia - Yasmin Fadhilla Ishma; Rita Myrna; Elisa Susanti (Borong Newinera Publisher, 2025)
Bureaucratic reform is a strategic step toward achieving effective and efficient governance. One key focus is simplifying bureaucracy by transitioning structural positions to functional ones, as mandated in Presidential Regulation No. 18 of 2020 on the 2020–2024 RPJMN. This study employs a descriptive method with a literature study approach to analyze the implementation of this policy in institutional, human resources (HR), and administrative management aspects. The analysis highlights three main challenges. First, institutional changes often lead to function duplication and workload misalignment. Second, in the HR aspect, gaps in ASN competency for functional roles persist, alongside negative perceptions of these positions. Third, while digitalization accelerates work processes, ASN performance management remains suboptimal. To address these challenges, a holistic approach is recommended to design adaptive policies that enhance organizational efficiency, effectiveness, and accountability. Bureaucratic reform must remain focused on improving the quality of public services, ensuring governance achieves its ultimate goal.